Strategies for the preparation of polymer composites with complex alignment of the dispersed phase - Adriana Sierra-Romero; Biqiong Chen (Nanocomposites, 2018)
The design and production of anisotropic composites and nanocomposites has become increasingly relevant in materials science and engineering because they provide an opportunity of enhancing and adapting the properties of a material for specialized applications. This article reviews the strategies that have been developed to achieve anisotropy based on the position and orientation of the dispersed phase in polymer composites including polymer nanocomposites. Flow and electric field-driven alignment methodologies are briefly described, which is followed by a focus on magnetically oriented composites. The use of magnetic fields for this purpose has been of particular interest in recent years due to its ease of use and the variety of materials on which this method can be applied. Strong magnetic fields are required to align diamagnetic fillers. However, the modification of particles with low magnetic susceptibilities with magnetic nanoparticles (i.e. iron oxide nanoparticles) has been proven to be a successful approach to broaden the capabilities of magnetic alignment in polymer composites. The development of filler manipulation techniques opens the possibility to mimic complex biological structures that promise to improve the mechanical properties of bioinspired composites and even achieve advanced functionalities in self-shaping materials for example.